High permeability membrane for oxygen separation and fabrication method thereof
Patent Information
- Application Number
- KR1020210045783
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-08
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2041-04-08
Smart Images

Figure 112021041218924-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a gas separation membrane, and more specifically, to a highly permeable oxygen permeable separation membrane having high oxygen permeability and a method for manufacturing the same. Background Technology
[0002] Oxygen transport membranes (OTMs) are a technology that selectively separates only oxygen from air when they possess both ionic and electronic conductivity at high temperatures and a chemical potential exists due to the difference in oxygen partial pressure between their ends. They are receiving significant attention as they can be applied to pure oxygen combustion systems to produce the high-purity oxygen required for combustion. For oxygen transport membranes to be applied in industry, a capacity of 5 to 10 mL·cm² is required. -2 ·min -1 Because high oxygen permeability of must be ensured, Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ Single-phase membranes with perovskite oxide structures containing cobalt or alkaline earth metals, such as (BSCF), and exhibiting high oxygen permeability are the most widely studied.
[0003] However, perovskite oxides are not only mechanically and chemically unstable, but also face difficulties in industrial applications due to performance degradation when CO2 is supplied to the permeable surface. In addition, 20×10 -6 K -1The aforementioned high coefficient of thermal expansion causes cracking and delamination in oxygen membranes, and the formation of carbonates in a CO2 atmosphere is a major factor in the reduction of oxygen permeability. To address these issues with single-phase membranes, research is being conducted on composite membranes utilizing fluorite-structured oxide materials with high chemical and mechanical stability as oxygen ion conductors and perovskite or spinel oxides as electron conductors. However, since the surface exchange reaction and bulk diffusion coefficients of fluorite-structured oxides are generally lower than those of perovskite oxide materials, the addition of fluorite-structured oxide materials to composite membranes leads to a decrease in oxygen permeability. Consequently, as there is a trade-off between oxygen permeability and stability, satisfying high oxygen permeability while maintaining mechanical and chemical stability presents a challenge in designing oxygen membrane materials applicable to oxygen fuel systems.
[0004] U.S. Patent No. 6146445 relates to an oxygen ion-conducting gas separation membrane and discloses a composite separation membrane comprising cerium gadolinium oxide, a fluorite-based oxide, and lanthanum cobalt, a perovskite-based compound. However, the separation membrane composed of the presented materials and their compositional ratios exhibits relatively low oxygen permeability, and the manufacturing method of the materials used is also complex.
[0005] Therefore, a high-permeability oxygen separation membrane manufactured with an optimal membrane composite composition ratio and a simplified membrane manufacturing method is required. Prior art literature
[0006] U.S. Patent No. 6146445 The problem to be solved
[0007] The objective of the present invention is to form a composite layer in which an electron-conducting material and an ion-conducting material are mixed, wherein the composite composition ratio of the electron-conducting material and the ion-conducting material is controlled to form a dense structure, and wherein on one or both sides of the composite layer, SrCo is formed using niobium-doped strontium cobaltite. 0.1 Fe 0.8 Nb 0.1 O 3-δ The present invention aims to provide a highly permeable oxygen permeable separator with improved mechanical and thermal stability and high oxygen permeability by coating (0≤δ<1) as a porous electrode active layer, and a method for manufacturing the same. means of solving the problem
[0008] To achieve the above objective, the high-permeability oxygen permeable separator is characterized by comprising a composite layer composed of a composite of an electron-conducting material and an ion-conducting material, and a porous electrode active layer formed on one or both sides of the composite layer.
[0009] In the high-permeability oxygen permeable membrane of the present invention, the composite layer may be composed of a composite in which the electron-conducting material and the ion-conducting material are mixed in a volume ratio of 8:2 to 2:8.
[0010] The above-mentioned electron-conducting material may be one or more selected from the group consisting of lanthanum strontium ferrite (LSF), lanthanum strontium manganite (LSM), lanthanum strontium cobaltite (LSC), lanthanum strontium chromite (LSCr), lanthanum strontium cobalt ferrite (LSCF), manganese ferrite (MnFe2O4), and nickel ferrite (NiFe2O4).
[0011] The above ion-conducting material may be one or more selected from the group consisting of gadolinia-doped ceria (GDC), samaria-doped ceria (SDC), and yttria-stabilized ceria (YDC).
[0012] The above porous electrode active layer is SrCo 0.1 Fe 0.8 Nb 0.1 O 3-δ Includes (0≤δ<1).
[0013] The thickness of the above composite layer may be 20㎛ to 300㎛.
[0014] In addition, the method for manufacturing a highly permeable oxygen permeable membrane according to the present invention for achieving the above-mentioned purpose is characterized by comprising the steps of: (a) manufacturing a composite layer comprising an electron-conducting material and an ion-conducting material; (b) sintering the composite layer; and (c) forming a porous electrode active layer on one or both sides of the composite layer.
[0015] In the method for manufacturing a highly permeable oxygen permeable membrane of the present invention, step (a) may form a composite in which the electron-conducting material and the ion-conducting material are mixed in a volume ratio of 8:2 to 2:8, and the composite layer may be manufactured using a tape casting process.
[0016] In step (a) above, the electron-conducting material may be one or more selected from the group consisting of lanthanum strontium ferrite (LSF), lanthanum strontium manganite (LSM), lanthanum strontium cobaltite (LSC), lanthanum strontium chromite (LSCr), lanthanum strontium cobalt ferrite (LSCF), manganese ferrite (MnFe2O4), and nickel ferrite (NiFe2O4).
[0017] In step (a) above, the ion-conducting material may be one or more selected from the group consisting of gadolinia-doped ceria (GDC), samaria-doped ceria (SDC), and yttria-stabilized ceria (YDC).
[0018] Step (b) above involves sintering the composite layer at 1200°C to 1400°C to form a sintered body.
[0019] The thickness of the composite layer formed through the method for manufacturing a high-permeability oxygen permeable separation membrane of the present invention may be 20㎛ to 300㎛.
[0020] The above step (c) is SrCo 0.1 Fe 0.8 Nb 0.1 O 3-δ A porous electrode active layer is formed by coating one or both sides of the composite layer with a material containing (0≤δ<1). Effects of the invention
[0021] The high-permeability oxygen-permeable membrane of the present invention has the advantage of a simple manufacturing process and easy sintering, as a composite layer in which an electron-conducting material and an ion-conducting material are mixed can be produced through tape casting.
[0022] Accordingly, the high-permeability oxygen permeable separator of the present invention manufactured has excellent mechanical and thermal stability as well as high oxygen permeability. In addition, by using niobium-doped strontium cobaltite as the electrode active layer, it has the effect of excellent chemical stability even in a CO2 atmosphere.
[0023] Therefore, the high-permeability oxygen permeable membrane of the present invention is easy to apply to industrial facilities equipped with four-terminal reactors that utilize flue gases such as carbon dioxide. Optimization of the oxygen membrane material composition and these oxygen permeability characteristics enable various combined power generation and combustion technologies depending on the environment of the pure oxygen generator. Brief explanation of the drawing
[0024] FIG. 1 is a schematic cross-sectional view of a highly permeable oxygen permeable membrane according to one embodiment of the present invention. Figure 2 is a flowchart of the method for manufacturing a high-permeability oxygen permeable membrane according to the present invention. Figure 3 is a graph showing the oxygen permeability measurement results of an oxygen permeable membrane according to Experimental Example 1 of the present invention. Figure 4 is a graph showing the results of evaluating the chemical stability of the oxygen permeable membrane of Example 1 in a CO2 atmosphere according to Experimental Example 2 of the present invention. Figures 5a and 5b are graphs showing the oxygen permeation behavior according to CO2 supply time in the oxygen permeation membranes of Example 1 and Comparative Example 1 according to Experimental Example 2 of the present invention. Figure 6 is a graph showing the oxygen permeability measurement results according to the temperature cycle of the oxygen permeable membrane of Example 1 according to Experimental Example 3 of the present invention. Specific details for implementing the invention
[0025] Prior to the detailed description of the present invention, the terms and words used in the specification and claims described below should not be interpreted as being limited to their ordinary or dictionary meanings. Accordingly, the embodiments described in this specification and the configurations illustrated in the drawings are merely the most preferred embodiments of the present invention and do not represent all of the technical ideas of the present invention; therefore, it should be understood that various equivalents and modifications capable of replacing them may exist at the time of filing this application.
[0026] Herein, in the overall drawings for explaining embodiments of the present invention, elements having the same function are denoted by the same reference numerals, and detailed descriptions thereof are omitted. Hereinafter, the high-permeability oxygen permeable membrane of the present invention will be described with reference to the attached drawings as follows.
[0027] The present invention is a highly permeable oxygen permeable separator comprising a composite layer and a porous electrode active layer. The composite layer controls the composite composition ratio of the electron-conducting phase and the ion-conducting phase, forms a dense structure, and in particular, on one or both sides of the composite layer, a niobium-doped strontium cobaltite (SrCo), also known as SCFN, is a material stable in a CO2 atmosphere. 0.1 Fe 0.8 Nb 0.1 O 3-δ (0≤δ<1) can be achieved simultaneously with maximum efficiency in electron and oxygen permeability through a porous electrode active layer coating.
[0028] In the present invention, a separation membrane can be defined as an interphase made of a material that has the function of selectively restricting the movement of substances between two phases. Gas separation using a separation membrane proceeds based on the principle of selective gas permeation through the membrane. In the oxygen-permeable separation membrane of the present invention, when a gas mixture comes into contact with the membrane surface, oxygen dissolves and diffuses into the separation membrane. Here, the driving force for gas separation is the partial pressure difference of the oxygen component applied across the two ends of the oxygen-permeable separation membrane.
[0029] FIG. 1 is a schematic cross-sectional view of a highly permeable oxygen permeable membrane according to one embodiment of the present invention.
[0030] As illustrated in FIG. 1, the high-permeability oxygen permeable separator (30) comprises a composite layer (10) made of an electron-ion mixed conductive phase in which an electron conductive phase or an ion conductive phase is mixed, and a porous electrode active layer (20) that improves oxygen permeability, wherein the composite layer is an ion-electron composite conductive layer capable of conducting ions and electrons in combination.
[0031] The above-mentioned electron-conducting phase is a perovskite-based material, which is an electron-conducting oxide, for example, strontium titanium ferrite (SrTi 1-x Fe x O 3-δ , where 0.05≤x≤0.80, STF), it is preferable to use one or more selected from the group consisting of lanthanum strontium ferrite (LSF), lanthanum strontium manganite (LSM), lanthanum strontium cobaltite (LSC), lanthanum strontium chromite (LSCr), lanthanum strontium cobalt ferrite (LSCF), manganese ferrite (MnFe2O4), and nickel ferrite (NiFe2O4).
[0032] The above ion-conducting phase preferably uses one or more selected from the group consisting of fluorite-based materials, such as yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samaria-doped ceria, strontium and magnesium-doped lanthanum gallates (LSGM), and bismuth oxide (Bi2O3).
[0033] In one embodiment, the composite layer of the oxygen permeable membrane of the present invention preferably uses lanthanum strontium cobalt ferrite (LSCF) as the electron-conducting material and GDC (Gd-doped Ceria), a fluorite structure oxide, as the ion-conducting material. In particular, to improve mechanical and chemical stability, a composite membrane rich in GDC of the ion-conducting material may be used.
[0034] The composite composition ratio of the above composite layer can be formed by mixing the electron-conducting phase and the ion-conducting phase in a volume ratio of 8:2 to 2:8, preferably 8:2 to 6:4, by a conventional powder mixing method, and more preferably, in a volume ratio of 3:7. Here, if the mixing ratio of the electron-conducting phase and the ion-conducting phase deviates from the range presented above, the electron-conducting phase and the ion-conducting phase may not properly form a composite structure, resulting in improper conduction of ions and electrons and a failure to improve the thermal, mechanical, and chemical stability of the oxygen permeable membrane.
[0035] In one embodiment, GDC having high mechanical strength as an oxygen ion conductor was added up to 70% when using lanthanum strontium cobalt ferrite (LSCF), an electronic conductive phase, within the electronic percolation limit of the composite membrane.
[0036] The thickness of the above composite layer is 20㎛ to 300㎛, and while a thickness of less than 20㎛ is possible, it is preferable to have a thickness of 20㎛ or more considering the ease of the manufacturing process and the mechanical strength of the manufactured oxygen separation membrane, and it is preferable not to have a thickness of more than 300㎛ considering the oxygen permeability.
[0037] The high-permeability oxygen permeable membrane of the present invention can control the thickness of the oxygen permeable membrane by considering the characteristic thickness (Lc=D / k), which is the relationship between internal diffusion (D) and surface exchange reaction (k) of the membrane, in order to secure high oxygen permeability. When the membrane is sufficiently thick, oxygen permeability is mainly determined by internal diffusion. However, as the thickness of the membrane gradually decreases below the characteristic thickness, the surface exchange reaction becomes dominant in determining oxygen permeability. Therefore, when the thickness of the membrane is less than the characteristic thickness, oxygen permeability can be improved by introducing a porous electrode active layer.
[0038] The porous electrode active layer of the present invention acts as a catalyst for the ionization of oxygen and the gasification reaction of oxygen ions, and in particular, perovskite oxide can be used as a stable active coating material in a CO2 atmosphere.
[0039] The porous electrode active layer of the present invention is SrCoO 3-δ SrCo with Fe and niobium (Nb) doped at the B-site in a perovskite oxide structure 0.1 Fe 0.8 Nb 0.1 O 3-δ(SCFN) can be used. In particular, niobium (Nb) with a high oxidation state can increase the acidity of the material to maintain the stability of the perovskite structure, thereby improving the chemical stability of the membrane and simultaneously ensuring high oxygen permeability.
[0040] The above SrCo 0.1 Fe 0.8 Nb 0.1 O 3-δ In this case, δ represents oxygen deficiency and varies depending on the dopant, and it is preferable that the range be 0≤δ<1.
[0041] In the present invention, it is preferable that the thickness of the porous electrode active layer be 13% to 134% of the thickness of the composite layer when the thickness of the composite layer is set to 100%.
[0042] If the thickness of the porous electrode active layer is less than 13% of the thickness of the composite layer, a problem may arise in which the increase in oxygen permeability due to coating on the composite layer is insufficient, and if it exceeds 134%, a problem may arise in which the diffusion rate of gas molecules within the coating layer is insufficient.
[0043] For example, the thickness of the porous electrode active layer is preferably 1 to 100 μm. If the thickness is less than 1 μm, a triple boundary phase is not sufficiently formed, which may inhibit the surface exchange reaction in the composite layer, and if it exceeds 100 μm, gas molecules cannot achieve a sufficient diffusion rate within the porous electrode active layer, and a problem of easy delamination may occur.
[0044] The present invention manufactures a high-permeability oxygen permeable membrane by using tape casting technology to produce a composite layer and coating a conductive active layer on both sides of the produced composite layer. A schematic flowchart of the method for manufacturing a high-permeability oxygen permeable membrane according to the present invention is shown in FIG. 2.
[0045] As shown in FIG. 2, a highly permeable oxygen permeable separator is formed in the order of (a) manufacturing a composite layer including an electron-conducting material and an ion-conducting material (S110), (b) sintering the composite layer (S120), and (c) forming a porous electrode active layer on one or both sides of the composite layer (S130).
[0046] Step (a) (S110) above manufactures a composite layer by mixing electron-conducting phase and ion-conducting phase materials using a tape casting process to form a composite that is an electron-ion mixed conductive phase. The manufacturing method of the composite layer is simplified through the tape casting process, and the thickness control and continuous production of the composite layer are facilitated.
[0047] Next, step (b) (S120) involves sintering the composite layer prepared in step (a) (S110) at a sintering temperature of 1200°C to 1400°C for 2 to 6 hours to produce a densified sintered body, and preferably, the composite layer can be sintered at 1300°C for 4 hours.
[0048] In the above step (b) (S120), if the sintering temperature presented as the sintering condition is less than 1200℃ and the sintering time is less than 2 hours, the mixture is not sufficiently sintered, resulting in a problem where the composite is not dense and the bonding strength is insufficient. If the sintering temperature exceeds 1400℃ and the sintering time exceeds 6 hours, the sintering proceeds excessively and the efficiency of the manufacturing process in terms of energy is reduced, which is undesirable.
[0049] (c) Step (S130) is a step of coating a porous electrode active layer on one or both sides of the composite layer sintered through Step (b) (S120), wherein the porous electrode active layer is SrCo 0.1 Fe 0.8 Nb 0.1 O 3-δ (SCFN) may include 0≤δ<1.
[0050] The porous electrode active layer may be coated on one or both sides of the composite layer, and preferably, it may be coated symmetrically or asymmetrically on both sides of the composite layer using a brush, spray, screen printing, tape casting, lamination process, etc. Additionally, the porous electrode active layer may be formed by coating on the entire or part of the surface of the composite layer.
[0051] Here, symmetry means that the porous electrode active layer is structurally symmetrically formed on both sides of the composite layer with respect to the composite layer.
[0052] After the above step (c) (S130), the method may further include a step of firing the porous electrode active layer at 800°C to 1200°C for 1 to 5 hours to increase the adhesion between the coated porous electrode active layer and the composite layer, and more preferably, it is preferable to fire at 1000°C for 3 hours.
[0053] If the firing temperature of the porous electrode active layer is less than 800℃, the adhesion between the composite layer and the porous electrode active layer is not properly achieved due to the low temperature, and if the firing temperature exceeds 1200℃, it is not desirable because a large amount of thermal energy is required due to the excessively high temperature, which reduces the efficiency of the manufacturing process.
[0054] Hereinafter, examples, comparative examples, and experimental examples are presented to aid in understanding the present invention. However, the following examples, comparative examples, and experimental examples are provided merely to facilitate a better understanding of the present invention, and the present invention is not limited to the following examples, comparative examples, and experimental examples.
[0055] Example 1 describes the preparation of a high-permeability oxygen-permeable membrane according to the present invention. In the high-permeability oxygen-permeable membrane, the composite layer was prepared using a mixed powder comprising GDC (Gd-doped Ceria) as the ion-conducting material and lanthanum strontium cobalt ferrite (LSCF) as the electron-conducting material. The mixed powder contains a relatively large amount of GDC for durability, and contains 70 volume% Ce based on the total volume of the mixed powder. 0.9 Gd 0.1 O 2-δ (GDC) : 30 volume% La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF) was manufactured and used.
[0056] A mixed powder of the above-mentioned GDC and LSCF, a binder, n-propyl acetate, ethanol, a dispersant, and a plasticizer were mixed and ball-milled for 48 hours to prepare a tape casting slurry. The prepared tape casting slurry was cast using a casting device to form a green sheet, and the thickness of the composite layer was adjusted under a temperature of 70°C and a pressure of 10 MPa. To densify the composite layer, the composite layer was prepared by sintering at 1300°C for 4 hours. The density of the composite layer after sintering was investigated by the Archimedes method, and the investigation results confirmed that the relative density of the composite layer corresponded to 98% of the theoretical density.
[0057] Next, SrCo to be used as the porous electrode active layer 0.1 Fe 0.8 Nb 0.1 O 3-δSCFN was synthesized by a solid-state reaction. An SCFN coating paste was prepared by mixing the synthesized SCFN powder and an inorganic solvent (Heraeus, Germany) capable of dissolving the SCFN powder in a 3-roll milling machine (EXAKT 50, EXAKT, Germany). The coating paste was uniformly applied to the surface of the prepared composite layer using a brush, and the coated film was calcined at 1000°C for 3 hours to improve the adhesion between the porous electrode active layer and the composite layer, thereby producing an oxygen permeable separator.
[0058] Comparative Example 1 is Ba, which is known to have high surface exchange kinetics among conventionally reported electrode active layer materials, used as the porous electrode active layer in the high-permeability oxygen permeable separator of Example 1. 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ An oxygen permeable membrane was prepared in the same manner as in Example 1 above, except that (BSCF) was used.
[0059] Comparative Example 2 is an oxygen permeable separator in which only the composite layer is formed and the porous electrode active layer is not formed, and was prepared in the same way as the composite layer of Example 1.
[0060] The following experimental examples were performed to evaluate the performance of the oxygen permeable membranes prepared according to the above examples and comparative examples.
[0061] Experimental Example 1 tested the oxygen permeability performance of a high-permeability oxygen permeable membrane prepared according to Example 1 above. The oxygen permeability was measured by gas chromatography (ACME 6000, YoungLin, Korea) after placing the membrane sintered on an alumina tube with glass sealant. As the supply and permeate gases, 21 vol% oxygen (O2) : 79 vol% nitrogen (N2) and high-purity helium gas (99.999%) were used, respectively, based on the total synthesis air. The flow rate was controlled by a mass flow meter, and the oxygen permeability was estimated from the oxygen concentration obtained by detecting the exhaust gas by gas chromatography.
[0062] In Experimental Example 1, the concentration of nitrogen (N2) generated in the exhaust gas was less than 1%, which indicated that the effect of gas leakage was negligible.
[0063] Oxygen permeability was measured according to the type used as the porous electrode active layer of the oxygen permeable separator, and the results are shown in Fig. 3.
[0064] Figure 3 is a graph showing the oxygen permeability measurement results of an oxygen permeable membrane according to Experimental Example 1 of the present invention.
[0065] In the case of Comparative Example 2, which is an oxygen permeable separator consisting only of a composite layer without a porous electrode active layer coating, 0.39 mL·cm at 900℃ -2 ·min -1 Although it exhibited very low oxygen permeability, Example 1, an oxygen permeable separator coated with a porous electrode active layer made of SCFN, showed an improved oxygen permeability of about 60 times or more compared to Comparative Example 2.
[0066] The transmittance of Example 1 is 6.3 mL·cm at 900°C. -2 ·min -1 It was measured as, and the peak oxygen permeability was 10.4 mL·cm at 1000℃. -2 ·min -1It reached up to. In the case of Comparative Example 1, which is an oxygen-permeable separator coated with a BSCF porous electrode active layer, the oxygen permeability was 8.8 mL·cm at 900°C. -2 ·min -1 It was shown to be, with a maximum of 10.80 mL·cm at 950℃. -2 ·min -1 It was measured as . Such oxygen permeability results are 5 to 10 mL·cm⁻¹, which is required for the oxygen permeable membrane of Example 1 to be applied in industry. -2 ·min -1 This is a result that can satisfy the high oxygen permeability of.
[0067] Experimental Example 2 measured the oxygen permeability according to temperature when carbon dioxide (CO2) was supplied to the permeation surface to evaluate not only the improvement of oxygen permeability, which is a key performance of the oxygen permeable membrane, but also the chemical stability of the membrane operating in a CO2 atmosphere. The results are shown in Figures 4 and 5.
[0068] Figure 4 is a graph showing the results of evaluating the chemical stability of the high-permeability oxygen permeable separator of Example 1 in a CO2 atmosphere according to Experimental Example 2 of the present invention, showing the oxygen permeability when hydrogen (He) gas and carbon dioxide (CO2) gas are supplied to Example 1, which is an oxygen permeable separator coated with a porous electrode active layer made of SCFN.
[0069] As shown in Fig. 4, oxygen permeability decreased when CO2 gas was supplied; however, this is attributed to the chemical absorption of oxygen ions onto the membrane surface, which reduced the oxygen chemical potential across the membrane. When CO2 gas was supplied, the oxygen permeability was 4.10 mL·cm at 900°C. -2 ·min -1 It was measured at 950 ℃ and 5.5 mL·cm -2 ·min -1 The maximum oxygen permeability of was measured. This result satisfies the range for industrial application of oxygen permeability.
[0070] Figures 5a and 5b are graphs showing the oxygen permeation behavior according to CO2 supply time in the oxygen permeation membranes of Example 1 and Comparative Example 1 according to Experimental Example 2 of the present invention.
[0071] Figure 5a shows the oxygen permeation behavior over time in the oxygen permeable membrane of Example 1 when CO2 is supplied to the permeable surface. As shown in Figure 5a, the oxygen permeability exhibits high CO2 stability for more than 200 hours at 850 °C.
[0072] However, as shown in Fig. 5b, the oxygen permeability of Comparative Example 1, which is an oxygen permeable separator coated with a porous electrode active layer made of BSCF, showed a rapid deterioration in permeability in a CO2 atmosphere due to the chemical instability of CO2.
[0073] For oxygen permeable membranes operating at high temperatures, thermodynamic stability along with high oxygen permeability is an essential element. Accordingly, in Experimental Example 3, the change in oxygen permeability according to a temperature cycle was measured to evaluate the thermal and mechanical stability of the oxygen permeable membrane of the present invention. The oxygen permeability of the oxygen permeable membrane of Example 1 was measured at rapid heating and cooling rates in a temperature cycle ranging from 900°C to 500°C. The results are shown in Fig. 6.
[0074] As shown in Fig. 6, despite a rapid thermal cycling rate of 20°C / min, the coated composite membrane exhibits significantly stable oxygen permeability, which is considered to indicate that the membrane is thermally and mechanically stable without peeling or cracking.
[0075] The present invention relates to a conventional porous electrode active layer Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δThis is intended to improve the problem that oxygen permeable membranes using (BSCF) exhibit high oxygen permeable flux but are not suitable for application in fuel systems in actual CO2 atmospheres because secondary phases such as barium carbonate (BaCO3) are formed due to the chemical instability of CO2 in CO2 atmospheres.
[0076] As previously discussed, in the case of the high-permeability oxygen-permeable membrane of the present invention, a dense structure is formed by manufacturing a composite layer in which an electron-conducting material and an ion-conducting material are mixed through tape casting, which is a simple process, and SrCo 0.1 Fe 0.8 Nb 0.1 O 3-δ By coating a porous electrode active layer composed of (SCFN), not only is high electron and oxygen permeability improved, but excellent chemical stability against a CO2 atmosphere and mechanical and thermal stability are also demonstrated, so it is expected to be widely used in industry. Explanation of the symbols
[0077] 10: Complex layer 20: Porous electrode active layer 30: High-permeability oxygen-permeable membrane
Claims
Claim 1 An oxygen permeable separator comprising: a composite layer composed of a composite of an electron-conducting material and an ion-conducting material mixed together; and a porous electrode active layer formed on one or both sides of the composite layer, wherein the porous electrode active layer is SrCo 0.1 Fe 0.8 Nb 0.1 O 3-δ A highly permeable oxygen permeable membrane characterized by including (0≤δ<1), wherein the composite layer is composed of a composite in which the electron-conducting material and the ion-conducting material are mixed in a volume ratio of 8:2 to 2:8, wherein the thickness of the oxygen permeable membrane is controlled by considering the characteristic thickness (Lc=D / k), which is the relationship between internal diffusion (D) and surface exchange reaction (k) of the membrane, wherein the thickness of the porous electrode active layer is 13% to 134% of the thickness of the composite layer, and the thickness of the composite layer is 20㎛ to 300㎛. Claim 2 A highly permeable oxygen permeable separation membrane according to claim 1, characterized in that the composite layer is composed of a composite in which the electron-conducting material and the ion-conducting material are mixed in a volume ratio of 8:2 to 2:
8. Claim 3 A highly permeable oxygen permeable membrane according to claim 1, characterized in that the electron-conducting material is one or more selected from the group consisting of lanthanum strontium ferrite, lanthanum strontium manganite, lanthanum strontium cobaltite, lanthanum strontium chromite, lanthanum strontium cobalt ferrite, manganese ferrite (MnFe2O4), and nickel ferrite (NiFe2O4). Claim 4 A highly permeable oxygen permeable membrane according to claim 1, characterized in that the ion-conducting material is one or more selected from the group consisting of gadolinia-doped ceria, samaria-doped ceria, and yttria-stabilized ceria. Claim 5 delete Claim 6 A high-permeability oxygen permeable separation membrane according to claim 1, characterized in that the thickness of the composite layer is 20㎛ to 300㎛. Claim 7 A method for manufacturing an oxygen permeable separator comprising: a composite layer composed of a composite material in which an electron-conducting material and an ion-conducting material are mixed; and a porous electrode active layer formed on one or both sides of the composite layer, wherein the method comprises: (a) a step of manufacturing the composite layer comprising the electron-conducting material and the ion-conducting material; (b) a step of sintering the composite layer; and (c) a step of forming a porous electrode active layer on one or both sides of the composite layer, wherein step (c) is SrCo 0.1 Fe 0.8 Nb 0.1 O 3-δ A method for manufacturing a highly permeable oxygen permeable membrane, characterized in that a porous electrode active layer is formed by coating a material containing (0≤δ<1) on one or both sides of the composite layer, and in step (a), a composite is formed by mixing the electron-conducting material and the ion-conducting material in a volume ratio of 8:2 to 2:8 and manufacturing the composite layer using a tape casting process, and the thickness of the oxygen permeable membrane is controlled by considering the characteristic thickness (Lc=D / k), which is the relationship between internal diffusion (D) and surface exchange reaction (k) of the membrane, wherein the thickness of the porous electrode active layer is 13% to 134% of the thickness of the composite layer and the thickness of the composite layer is 20㎛ to 300㎛. Claim 8 A method for manufacturing a highly permeable oxygen permeable separation membrane according to claim 7, wherein step (a) comprises forming a composite in which the electron-conducting material and the ion-conducting material are mixed in a volume ratio of 8:2 to 2:8 and manufacturing the composite layer using a tape casting process. Claim 9 A method for manufacturing a highly permeable oxygen permeable membrane according to claim 7, wherein the electron-conducting material is one or more selected from the group consisting of lanthanum strontium ferrite, lanthanum strontium manganite, lanthanum strontium cobaltite, lanthanum strontium chromite, lanthanum strontium cobalt ferrite, manganese ferrite (MnFe2O4), and nickel ferrite (NiFe2O4). Claim 10 A method for manufacturing a highly permeable oxygen permeable membrane according to claim 7, wherein the ion-conducting material is one or more selected from the group consisting of gadolinia-doped ceria, samaria-doped ceria, and yttria-stabilized ceria. Claim 11 A method for manufacturing a highly permeable oxygen permeable separation membrane according to claim 7, wherein step (b) is characterized by sintering the composite layer at 1200°C to 1400°C. Claim 12 delete Claim 13 A method for manufacturing a highly permeable oxygen permeable separation membrane, characterized in that, in claim 7, the thickness of the composite layer is 20㎛ to 300㎛. Claim 14 A method for manufacturing a highly permeable oxygen permeable separator, characterized in that, in claim 7, after step (c), the porous electrode active layer is calcined at 800°C to 1200°C.
Citation Information
Patent Citations
High permeability membrane for oxygen separation and fabrication method thereof
KR101806365B1
High permeability membrane for oxygen separation and fabrication method thereof
KR1020160117900A
High permeability membrane coated electroactive layer on both sides for oxygen separation and fabrication method thereof
KR1020170002877A
